The Automaticity of Race and Afrocentric Facial Features in Social Judgments. (article). - Blair, Irene V.
Four experiments were conducted to examine the automaticity of stereotyping based on racial category and (within-race). Afrocentric facial features. Results showed that both forms of stereotyping are efficient processes, able to operate when cognitive resources are highly restricted. The 2 differed, however, in their controllability, Participants demonstrated that they were sensitized to race-based stereotypes and able to control that influence to a significant degree. In contrast, participants appeared to be largely unaware of using Afrocentric features to make stereotypic inferences, and they p